SMN post-translational modifications in spinal muscular atrophy - Riboldi, Giulietta M.; Faravelli, Irene; Rinchetti, Paola; Lotti, Francesco (Frontiers in Cellular Neuroscience, 2023)
Since its first identification as the gene responsible for spinal muscular atrophy (SMA), the range of survival motor neuron (SMN) protein functions has increasingly expanded. This multimeric complex plays a crucial role in a variety of RNA processing pathways. While its most characterized function is in the biogenesis of ribonucleoproteins, several studies have highlighted the SMN complex as an important contributor to mRNA trafficking and translation, axonal transport, endocytosis, and mitochondria metabolism. All these multiple functions need to be selectively and finely modulated to maintain cellular homeostasis. SMN has distinct functional domains that play a crucial role in complex stability, function, and subcellular distribution. Many different processes were reported as modulators of the SMN complex activities, although their contribution to SMN biology still needs to be elucidated. Recent evidence has identified post-translational modifications (PTMs) as a way to regulate the pleiotropic functions of the SMN complex. These modifications include phosphorylation, methylation, ubiquitination, acetylation, sumoylation, and many other types. PTMs can broaden the range of protein functions by binding chemical moieties to specific amino acids, thus modulating several cellular processes. Here, we provide an overview of the main PTMs involved in the regulation of the SMN complex with a major focus on the functions that have been linked to SMA pathogenesis.